Attitudes on patient safety among Universiti Sains Malaysia (USM) medical students - Razali, Shazrina Ahmad (2020)
INTRODUCTION: World Health Organization (WHO) introduced a patient safety curriculum guide for medical schools worldwide since 2009 following realizing patient safety is a universal health concern. Even though, medical schools agreed on the impact of patient safety to nurture future healthcare professional, however lack of documentation on their implementation of patient safety curriculum in their medical training. The aim of this study is to explore attitudes and its associated factors on patient safety among Universiti Sains Malaysia (USM) undergraduate medical students. METHODOLOGY: A cross-sectional study was conducted among 457 Year 2 to Year 5 medical students. The attitudes on patient safety were measured using a validated tool, Attitudes to Patient Safety Questionnaire (APSQ) III on 7 points Likert scale. The APSQ III measures 9 domains; i) patient safety training received, ii) error reporting confidence, iii) working hours as error cause, iv) error inevitability, v) professional incompetence as error cause, vi) disclosure responsibility, vii) team functioning, viii) patient involvement in reducing error, and ix) importance of patient safety in the curriculum. Each domain was interpreted as positive, neutral, or negative attitudes. Six items were reverse coded. Statistical analysis independent t-test, oneway ANOVA and Pearson correlation test were performed using Statistical Package for Social Sciences (SPSS) version 24. RESULTS: A total of 427 (93.4% response rate) out of 457 medical students from Year 2 until Year 5 voluntarily participated in this study (6.6% drop out rate). Majority of them were female 290 (67.9%), age 21 years old and above 336 (78.7%), Year 2 126 (29.5%) and scored grade B+, grade pointer (3.33-3.66) 196 (45.9%). All were positive attitudes except for domain 5 (professional incompetence as error cause). The highest score was domain 7 (team functioning) and the lowest score was domain 5 (professional incompetence as error cause). Post-hoc analysis showed a significant mean difference of attitude to patient safety score and year of study among pre-clinical and clinical year students in five domains. There was poor positive correlation between age and domain 3 (working hours as error cause). There were also a poor positive correlation between academic performance for domain 3 (working hours as error cause) and domain 4 (error inevitability). However, attitudes on patient safety were not associated with gender. CONCLUSION: USM medical students had a positive attitude towards patient safety in general. However, there was still a room for improvement towards improvement of patient safety among medical students prior their practice as medical doctor. Therefore, patient safety curriculum need to be implemented as early as possible in the medical training. Hence, a proper documentation and a thorough curriculum review on patient safety curriculum in medical schools are crucial to ensure improvement of patient safety among medical doctors in future practise.